Comparative analysis of international melanoma guidelines - Ahmad Idrissi-Yaghir; Henning Schäfer; Hendrik Damm; Georg C. Lodde; Elisabeth Livingstone; Dirk Schadendorf; Christoph M. Friedrich (EJC Skin Cancer)
Purpose: Melanoma is an aggressive skin tumor known for its early spread through lymphatic and blood vessels. Over the past decades, significant advancements in surgical and therapeutic approaches have improved patient outcomes. While treatment recommendations are outlined in national clinical guidelines, these guidelines can differ from one country to another. Understanding the discrepancies in the referenced evidence across national guidelines can offer insights into the sources that inform their development. These insights may contribute to optimizing future diagnostic methods, treatment strategies, and follow-up care approaches. Methods: In this study, the cited references in ten international clinical practice guidelines for melanoma are compared using various bibliometric indicators, including journal impact factor, citation count, and publication characteristics such as publication type, to gain insights into the sources of evidence, collaboration patterns, and translational impact of the cited publications. Results: The analysis revealed discrepancies in the cited literature among international melanoma guidelines. For instance, the German guideline referenced 791 unique publications but shared less than 5 % of these with other guidelines. Although all guidelines addressed diagnostic methods, treatment options, and follow-up care, the minimal overlap in references indicates substantial variations in their evidence bases. Conclusion: This study highlights the importance of critically evaluating cited references in international melanoma guidelines, as it analyzed and found discrepancies in the number and quality of cited publications. These findings underscore the need for a more standardized approach to guideline development and enhanced international collaboration to improve the reliability and effectiveness of melanoma management recommendations.